Assessment of suitability of drinking water from the springs in Urban slums of Kampala - Kiwanuka, Moses; Mutanda, Hosea Eridadi; Niyomukiza, John Bosco; Nakasagga, Erinah (Environmental Challenges, 2023)
Any water source used for domestic purposes should meet World Health Organization water quality standards. In most slums of developing nations, water sources such as springs are critical to the residents. Although spring water is often considered fit for domestic use, poor sanitation practices in slums lead to faecal contamination of spring. The objectives of this study were to assess the faecal contamination risk factors and the water quality from the identified springs in Bwaise, Kampala in the dry and rainy seasons. Parameters that were considered in this study were: pH, Electrical conductivity, apparent colour, turbidity, hardness, Chloride, Nitrate, total coliform and E-coli. The cross-sectional sanitary risk assessment for all springs revealed faecal contamination risks. The physiochemical parameters were within the allowable limits of World Health Organization standards for drinking water in all seasons. E-coli values were between 1.35 -13.75Cfu/ 100ml in all seasons. Both total coliform and E- coli were above the permissible limit of o Cfu/100ml in all seasons. When the water samples were analyzed basing WQI, the indices revealed excellent water during the dry season and good water during the wet season. The index values were between 40.09 to 49.34 in the dry season and 54.24 to 74.17 in the wet season. Therefore, treatment or boiling before drinking should be encouraged in the community. Also, proper solid waste management and pit latrine construction strategies should be used in the area
Keywords: Springs; Faecal contamination; Water parameters; Water quality index